Outbreak of Pseudomonas aeruginosa infections after CT-guided spinal injections. (October 2021) - Paul, G.; Meißner, A.; Neuneier, J.; Neuschmelting, V.; Grau, S.; Yagdiran, A.; Scheyerer, M.J.; Malin, J.J.; Suárez, I.; Lehmann, C.; Exner, M.; Wiesmüller, G.A.; et al.
Summary: Background: Meningitis and spinal infections with Gram-negative bacteria after local injections for treatment of chronic back pain are rare. This study investigated an outbreak of Pseudomonas aeruginosa infections following computed tomography (CT)-guided spinal injections (SI). Methods: A case was defined as a spinal infection or meningitis with P. aeruginosa after SI between 10 th January and 1 st March 2019 in the same outpatient clinic. Patients without microbiological evidence of P. aeruginosa but with a favourable response to antimicrobial therapy active against P. aeruginosa were defined as probable cases. Findings: Twenty-eight of 297 patients receiving CT-guided SI during the study period developed meningitis or spinal infections. Medical records were available for 19 patients. In 15 patients, there was microbiological evidence of P. aeruginosa, and four patients were defined as probable cases. Two of 19 patients developed meningitis, while the remaining 17 patients developed spinal infections. The median time from SI to hospital admission was 8 days (interquartile range 2–23 days). Patients mainly presented with back pain ( N =18; 95%), and rarely developed fever ( N =3; 16%). Most patients required surgery ( N =16; 84%). Seven patients (37%) relapsed and one patient died. Although the source of infection was not identified microbiologically, documented failures in asepsis when performing SI probably contributed to these infections. Conclusions: SI is generally considered safe, but non-adherence to asepsis can lead to deleterious effects. Spinal infections caused by P. aeruginosa are difficult to treat and have a high relapse rate.